2018
DOI: 10.1001/jama.2018.3264
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lonafarnib Treatment vs No Treatment With Mortality Rate in Patients With Hutchinson-Gilford Progeria Syndrome

Abstract: Among patients with HGPS, lonafarnib monotherapy, compared with no treatment, was associated with a lower mortality rate after 2.2 years of follow-up. Study interpretation is limited by its observational design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 22 publications
1
163
0
4
Order By: Relevance
“…HGPS is due to the synthesis of progerin, which arises from abnormal LMNA splicing and subsequent abnormal post-translational maturation of mutated prelamin A. Progerin remains permanently farnesylated and forms an abnormal lamina network, tightly bound to the inner nuclear membrane [19,20]. Therapeutic trials using farnesyl transferase inhibitors showed evidence of cardiovascular benefit in patients with HGPS, in favor of a prominent pathophysiological role of the abnormal farnesyl moiety of progerin present in vascular cells [17,21], which is also supported by murine models [12,22,23]. Several studies, including ours, have shown that other LMNA pathogenic variants, responsible for atypical progeroid syndrome or FPLD2, could also lead to abnormal prelamin A accumulation, which could contribute to vascular senescence and atherosclerosis by targeting endothelial and/or vascular smooth muscle cells [4,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…HGPS is due to the synthesis of progerin, which arises from abnormal LMNA splicing and subsequent abnormal post-translational maturation of mutated prelamin A. Progerin remains permanently farnesylated and forms an abnormal lamina network, tightly bound to the inner nuclear membrane [19,20]. Therapeutic trials using farnesyl transferase inhibitors showed evidence of cardiovascular benefit in patients with HGPS, in favor of a prominent pathophysiological role of the abnormal farnesyl moiety of progerin present in vascular cells [17,21], which is also supported by murine models [12,22,23]. Several studies, including ours, have shown that other LMNA pathogenic variants, responsible for atypical progeroid syndrome or FPLD2, could also lead to abnormal prelamin A accumulation, which could contribute to vascular senescence and atherosclerosis by targeting endothelial and/or vascular smooth muscle cells [4,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that administration of sodium nitrate to HGPS mice (del Campo et al 2019) and administration of Lonafarnib, a farnesyltransferase inhibitor, to HGPS children reduce arterial stiffness (Gordon et al 2012;Gordon et al 2018). Furthermore, the reduction in arterial stiffness by lonafarnib was associated with an increased lifespan of HGPS children (Gordon et al 2018). These studies did not distinguish between effects on axial versus circumferential mechanics, nor are the mechanisms by which nitrate and lonafarnib reduce arterial stiffness fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…The first clinical trial using a farnesyltransferase inhibitor (FTI), lonafarnib, showed an improvement of cardiovascular phenotypes. Leslie B. Gordon (Progeria Research Foundation, USA) presented the latest results of the FTI trail, which was very encouraging in that mortality was reduced from 29.6% to 3.7% (untreated vs treated) during a 2.2 year follow-up (Gordon et al, 2018). Another trial with FTI and the mTOR inhibitor, everolimus, is ongoing.…”
Section: Hutchinson-gilford Progeria Syndromementioning
confidence: 99%